Effect and behaviour of different substrates in relation to the formation of aerobic granular sludge - Pronk, M. (Appl Microbiol Biotechnol, 2015)
When aerobic granular sludge is applied for industrial wastewater treatment, different soluble substrates can be present. For stable granular sludge formation on volatile fatty acids (e.g. acetate), production of storage polymers under anaerobic feeding conditions has been shown to be important. This prevents direct aerobic growth on readily available chemical oxygen demand (COD), which is thought to result in unstable granule formation. Here, we investigate the impact of acetate, methanol, butanol, propanol, propionaldehyde, and valeraldehyde on granular sludge formation at 35 °C. Methanogenic archaea, growing on methanol, were present in the aerobic granular sludge system. Methanol was completely converted to methane and carbon dioxide by the methanogenic archaeum Methanomethylovorans uponensis during the 1-h anaerobic feeding period, despite the relative high dissolved oxygen concentration (3.5 mg O(2) L(−1)) during the subsequent 2-h aeration period. Propionaldehyde and valeraldehyde were fully disproportionated anaerobically into their corresponding carboxylic acids and alcohols. The organic acids produced were converted to storage polymers, while the alcohols (produced and from influent) were absorbed onto the granular sludge matrix and converted aerobically. Our observations show that easy biodegradable substrates not converted anaerobically into storage polymers could lead to unstable granular sludge formation. However, when the easy biodegradable COD is absorbed in the granules and/or when the substrate is converted by relatively slow growing bacteria in the aerobic period, stable granulation can occur. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00253-014-6358-3) contains supplementary material, which is available to authorized users.